High resolution reverse-offset printed wearable laminated textile capacitive sensor for continuous monitoring of atopic dermatitis - Huanghao Dai; Alexandar R. Todorov; Sheng Yong; Russel Torah; Michael Ardern-Jones; Steve Beeby (npj Flexible Electronics)
Abstract Reverse-offset printing (ROP) enables microscale patterning on flexible substrates, making it ideal for fabricating interdigital capacitive (IDC) sensors for atopic dermatitis (AD) monitoring. AD, characterized by skin dryness and inflammation, demands precise hydration tracking. Tailoring IDC electrode gaps to 50 µm concentrates the electric field within the stratum corneum (SC), enhancing sensitivity beyond the capabilities of traditional screen printing. Finite element modelling and ROP were employed to assess the impact of electrode geometry and encapsulation thickness on sensor performance. Findings indicate that 50 µm electrodes with encapsulation layers under 10 µm maintain high sensitivity and consistent operation. A clinical case study demonstrated the 50 µm sensor’s ability to distinguish lesional from non-lesional skin. These results inform the optimization of encapsulation–performance balance and advance the design of wearable, high-resolution IDC sensors for continuous skin hydration monitoring in personalized dermatological care.